Proceedings of the Proceedings of the 2nd International Conference on Social Sciences, ICSS 2019, 5-6 November 2019, Jakarta, I 2020
DOI: 10.4108/eai.5-11-2019.2292491
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Islamic Work Ethics to Entrepreneurial Intention: The Study of Undergraduate Students in Indonesia

Abstract: Entrepreneurs is important bringing advancements of a country's economy, yet entrepreneurs are created not born. Previous researches acknowledged that entrepreneurship activities were intentional based and having strong relationship with individual's values or culture. As for Moslem, the inherent individual culture, is in form of Islamic Work Ethics, which should support entrepreneurship. This objective of this study is to reveal the role of Islamic Work Ethics in influencing entrepreneurial intention of Indon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Islamic values can increase entrepreneurial skills (entrepreneurship. Research conducted by Widana & Nurwati (2020) on undergraduate students from universities in Jakarta, Indonesia, also shows that there is a positive and significant correlation between Islamic work ethic and entrepreneurial intention. Rehan et al 2019did about the intention of entrepreneurship in the Muslim community in Pakistan also shows that there is an influence of religion on entrepreneurial intentions mainly due to Islamic values and religious practices.…”
Section: Islamic Work Ethic and Entrepreneurial Intentionmentioning
confidence: 91%
See 1 more Smart Citation
“…Islamic values can increase entrepreneurial skills (entrepreneurship. Research conducted by Widana & Nurwati (2020) on undergraduate students from universities in Jakarta, Indonesia, also shows that there is a positive and significant correlation between Islamic work ethic and entrepreneurial intention. Rehan et al 2019did about the intention of entrepreneurship in the Muslim community in Pakistan also shows that there is an influence of religion on entrepreneurial intentions mainly due to Islamic values and religious practices.…”
Section: Islamic Work Ethic and Entrepreneurial Intentionmentioning
confidence: 91%
“…Several studies have shown results that support this statement (Gerry et al, 2008, Giancomin, et al, 2011and Pruett et al, 2007). Apart from education and entrepreneurial experience, Rehan et al (2019), Kalid, et al, (2019), Widana & Nurwati, (2020) also found that values such as Islamic work ethic values have an influence on entrepreneurial intentions. Likewise, cultural factors are thought to also influence entrepreneurial intentions.…”
Section: Factors Affecting Intention (Intention) Entrepreneurshipmentioning
confidence: 99%